Nutritional Contribution of Awaous sp Small Indigeneous Fish Powder Important for the First 1000 Days of Life - Bahja, Bahja; Hartini, Diah Ayu; Ansar (Poltekkes Kemenkes Palu, 2023)
Research facts prove that small-sized fish are essential nutrition during the first 1000 days of life. Central Sulawesi Province has an endemic small-sized marine fish species locally known as duo or penja fish (Awaous sp), which has not been studied for its bio-mineral content. This study aimed to analyze the moisture, ash, protein, calcium, iron, and zinc content in Awaous sp protein flour. This research was a descriptive laboratory study conducted at the Ilmu Bahan Makanan Laboratory Department of Nutrition Poltekkes Kemenkes Palu and PT. Saraswanti Indo Genetech Laboratory, Bogor, West Java, from January to September 2023. The sampling technique used purposive sampling, which involved purchasing fish from the local market in Palu city. Awaous sp protein flour had a moisture, ash, protein, Ca, Fe, and Zn content of 3.89%, 9.71%, 73.53%, 2316.88 mg/100g, 24.54 mg/100g, and 8.97 mg/100g, respectively. The contribution per serving of 145 grams of Awaous sp fish flour met the nutritional requirements (Recommended Dietary Allowances - RDA) for protein, Ca, Fe, and Zn per person per day for infants aged 6-11 months, children aged 1-3 years, pregnant women, and lactating women. Awaous sp protein flour had higher protein and Fe content compared to other small fish and had the potential to meet RDA requirements. Therefore, consuming Awaous sp protein flour as part of the daily diet can be a suitable strategy to address nutritional deficiencies during the first 1000 days of life for residents in Central Sulawesi.